Intervenciones de enfermería en la prevención de sepsis neonatal en recién nacidos del área neonatología Hospital General Dr. Liborio Panchana Sotomayor, Provincia Santa Elena periodo mayo – septiembre 2019. - Morocho Pinela, Elina Narcisa (2019)
Neonatal sepsis is a complication that can be acquired from birth, caused by an infectious agent that is presented by different factors: neonatal, maternal, environmental and knowledge, where nursing interventions are essential for prevention. The objective is to identify nursing interventions for the prevention of Neonatal Sepsis in newborns of the Neonatology Area, Dr. Liborio Panchana General Hospital Santa Elena Province period May - September 2019. The research was qualitative-quantitative, using the inductive, deductive, historical-logical and analysis-synthesis method, with applied, field, descriptive and transversal research types, with information gathering techniques: survey and observation, the instruments: questionnaire and observation sheet applied to nurses and mothers of neonates in the neonatology area, with a sample of 65 infants admitted to the Dr. Liborio Panchana Sotomayor General Hospital. The result was that newborns with Neonatal Sepsis are mostly male with 75%, the average age is between 0-5 days with 57%, the weight of 1600-2400 grams with 43% and born with less of 37 weeks gestation with 80%. It was concluded that nursing interventions are of the utmost importance for the prevention of infections, for this, the necessary personnel must be had in a critical area and, above all, enough material to perform different procedures and to be able to apply the norms and protocols established by the Ministry of Public Health.